Analytical Investigations of Kinetic and Heat Transfer in Slow Pyrolysis of a Biomass Particle - Ojolo, S.J; Osheku, C.A.; Sobamowo, M.G (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
The utilization of biomass for heat and power generation has aroused the interest of most researchers especially those of energy .In converting solid fuel to a usable form of energy, pyrolysis plays an integral role. Understanding this very important phenomenon in the thermochemical conversion processes and representing it with appropriate mathematical models is vital in the design of pyrolysis reactors and biomass gasifiers. Therefore, this study presents analytical solutions to the kinetic and the heat transfer equations that describe the slow pyrolysis of a biomass particle. The effects of Biot number, temperature and residence time on biomass particle decomposition were studied. The results from the proposed analytical models are in good agreement with the reported experimental results. The developed analytical solutions to the heat transfer equations which have been stated to be â€œanalytically involvedâ€ showed average percentage error and standard deviations 0.439 and 0.103 from the experimental results respectively as compared with previous model in literature which gives average percentage error and standard deviations 0.75 and 0.106 from the experimental results respectively. This work is of great importance in the design of some pyrolysis reactors/units and in the optimal design of the biomass gasifiers.